Athlete Acclimatization: Its Impact on Health and Performance in Sports Competitions - A Literature Review - Nimrot Manalu; Tuppal Ajun Siburian; Hizkia Cauvin; Rival Gunawan; Sinis Parningotan (Joska: Jurnal Isori Kampar, 2025)
Objectives: This review examines the physiological processes of acclimatization in athletes competing in varied environmental conditions and evaluates its impact on health outcomes and performance metrics. The study specifically investigates the effectiveness of different acclimatization protocols and their application across different sports disciplines. Methods: A systematic review was conducted using five major databases (PubMed, SPORTDiscus, Web of Science, Embase, and Cochrane Library) from January 2010 to September 2024. The search strategy combined terms related to acclimatization, athletic performance, and environmental variables. Studies meeting inclusion criteria were independently assessed by two reviewers using the PEDro scale for quality assessment. Results: Seventy-eight studies met the inclusion criteria. Heat acclimatization protocols consistently demonstrated improved thermoregulation, cardiovascular stability, and performance metrics (3-7% improvement) when implemented 10-14 days before competition. Altitude acclimatization studies showed greatest benefit at moderate elevations (2000-2500m) with 2-3 week exposure periods. Cold acclimatization research revealed mixed results, with metabolic and perceptual adaptations being more prominent than performance enhancement. Cross-adaptation phenomena were identified in 23% of the analyzed studies, suggesting potential for combined protocols. Conclusion: Acclimatization protocols have statistically significant and practically meaningful impacts on athletic performance and health outcomes when properly implemented. Sport-specific protocols with progressive exposure yield optimal results. Future research should focus on individualized approaches and the interaction between acclimatization strategies and other performance factors such as nutrition and recovery protocols.